THE PEDAGOGICAL TOOLS FOR THE DEVELOPMENT OF COMPASSION OF THE PRIMARY SCHOOL CHILDREN WITH REGARD TO THEIR PSYCHOLOGICAL TYPES - Guseva, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article contains the development of pedagogical tools of the compassion in the primary school children in the educational process with regard to their psychotypes. It also includes examples of learning activities for primary school teachers.